Evaluation of Critical Thinking Disposition in Learning using E-Learning - Tukino Paryono; Gunawan Gunawan; Sutarto Sutarto; Danny Manongga (INTERNAL (Information System Journal), 2022)
Critical thinking disposition includes seven habits as a motivation in analyzing problems to make decisions in the online learning system applied at the University. E-Learning application as online learning media which is equipped with various facilities to support Lecturer activities.  The purpose of this study was to determine the differences in critical thinking disposition based on the gender of the lecturer and the level of the Lecturer's Academic Position.  The results of the analysis of the calculation of the average score on the evaluation of critical thinking dispositions based on the gender of women (M=3.02) and men (M=3.23) means that there are differences in critical thinking although relatively little. The difference is found in statements related to reading habits, digging and uploading material, easy to receive input, studying material, reviewing assignments and being open.  Meanwhile, the f-count value is 0.903 which is smaller than the f-table is 3.24 at p <0.50, this indicates that there is no significant difference in the Lecturer's Academic Position level in applying critical thinking dispositions in using E-Learning applications for the learning process. Two indicators, gender and Lecturer's Academic Position evaluated with 14 statements for 7 aspects have not shown significant differences, this provides an opportunity to be studied more deeply in compiling statement indicators and can be related to the development of Lecturer's critical thinking disposition with taxono bloom.